Efektivitas Kinerja LPKNI Dalam Perlindungan Konsumen Di Kota Jambi - Indah Cahyani, Novi; Alissa, Evalina (Universitas Jambi, Fakultas Hukum, 2026)
The role of non-governmental organizations such as LPKNI is also an important part of implementing consumer protection in Jambi City, however, the implementation is sometimes not in accordance with what is mandated in Law Number 8 of 1998 concerning Consumer Protection. This study examines consumer protection efforts by LPKNI in the city and the factors inhibiting the implementation of consumer protection in Jambi city. This research uses the Yuridical-Empirical research method which examines das sein and sollen between the provisions in Law Number 8 of 1998 concerning Consumer Protection and the reality in the field. The results of this study show that LPKNI carries out various tasks in organizing consumer protection ranging from consumer education, receiving various consumer complaints, to providing legal assistance. However, on the other hand, there are still many challenges faced by LPKNI.